Comparative Fatty Acid Profiling and Nutritional Assessment of Groundnut and Cashew Nut Oils - Maximus Mayer Ebulue (Bumi Publikasi Nusantara, 2025)
Fatty acids are vital components of biological membranes and key metabolic fuels in living organisms. Their composition influences the nutritional and functional properties of food. This study aimed to compare the fatty acid profiles of groundnut and cashew nut to determine their nutritional value. Using the AOAC in 2000 method, samples of both nuts were analysed through gas chromatography. Groundnut oil was found to contain higher concentrations of oleic acid (46.99%) and linoleic acid (9.91%), while cashew nut oil had higher levels of palmitic acid (22.88%) and lauric acid (18.98%). The total fatty acid concentration in groundnut exceeded that of cashew, indicating that groundnut is richer in fatty acids overall. This comparison highlights the superior fatty acid content of groundnut, which could inform nutritional recommendations and food formulation strategies. The findings contribute to food science literature by emphasizing the value of groundnut as a high-fatty-acid food source.